Chemical Composition and Antimicrobial Activity of Essential Oil Collected from Adhatoda vasica Leaves (Bangladesh Journal of Scientific and Industrial Research, 2011)
Essential oil obtained from hydrodistillation of Adhatoda vasica (Nees.) leaves was analyzed by gas chromatograph-mass spectrometer (GC-MS). Hydrodistillation of the Adhatoda vasica (Nees.) leaves yielded 0.096% (v/w) of essential oil. Eleven compounds comprising about 100% of the total oil were identified. The most abundant components of essential oil were 1,2,3, trimethyl benzene (1.51 %), borneol (58.60 %), ethanonaphthalene (2.82 %), 1,1,4a trimethyl-5,6-dimethylenedecahydro naphthalene (5.28 %), 2,tert-butyl-1,4- dimethoxy benzene (6.50 %), bicyclo[jundec-4-ene,4,11-trimethyl-8-methylene (14.56 %), hexa- methyl dewar benzene (0.87 %), alphacaryophyllene (1.95 %), cycloproplejazulene (1.48 %), caryophyllene oxide (2.35 %) and 2-naphthalenemethanol (1.46 %). The microbial activity of the oil was screened against Bacillus subtilis, Salmonella typhimurium, Staphylococcus aureus, and E. coli. It was found that all mentioned microorganisms were more or less sensitive to this essential oil. Key Words: Adhatoda vasica; Essential oil; Chemical composition; Antimicrobial activity. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8185 Bangladesh J. Sci. Ind. Res. 46(2), 191-194, 2011